Glossary of pollen and spore terminology - Punt, W.; Hoen, P.P.; Blackmore, S.; Nilsson †, S.; Le Thomas, A. (Review of palaeobotany and palynology, 2007)
The glossary of pollen and spore terminology was first presented to the international palynological community as the final outcome of the Working Group on Palynological Terminology at the 8th International Palynological Congress in Aix-en-Provence in 1992. It became widely accepted as reference guide for palynologists to assist in the preparation of accurate and consistent descriptions of their material. It also serves as a practical source of information for non-specialists who wish to understand the meaning of the large number of existing palynological terms. The history of the glossary began in 1972 at the 3rd IPC at Novosibirsk when the working group on palynology was established. Throughout its history the project has been a collaborative effort with contributions from many palynologists, representing all branches of the discipline. Only through this long and elaborate procedure, with input from many people, it has been possible to produce the glossary. The entries are arranged alphabetically and are accompanied by simple schematic illustrations where appropriate. These contain the minimum amount of information needed to explain the feature. Moreover, to simplify the recognition of pollen and spore wall layers, colours have been used to indicate the corresponding layers. The first edition had 547 terms of which 339 have been accepted and recommended for use. In the second edition, a further 41 terms have been added with their appropriate illustrations. Of these, 10 have been accepted and 31 rejected for a variety of reasons. Where necessary, illustrations have been revised. An extensive list of consulted literature has been added.